DOI PESONA LENGGOK DALAM BUDAYA SENI TRADISI SUNDA, STUDI KASUS PARADE SENI PERTUNJUKAN DALAM EVEN HUJAN KARYA #9 - Lousy Loustiawaty; Novianti, Irena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the representation of the cultural charm of lenggok in the collaborative art parade Hujan Karya #9 as a contemporary art response to cultural preservation challenges. Using a qualitative approach with a case study method, the study was conducted through direct observation, visual documentation, and aesthetic-based descriptive-interpretative analysis. The results indicate that lenggok is manifested interdisciplinarily through dance movements, the visual rhythm of fine arts, and the dynamics of fashion. The conclusion emphasizes the role of this collaboration as an effective cultural representation space in bridging tradition with modern art practices. This research recommends the development of similar models as a means of collaborative art learning and as a subject for further cultural and performing arts studies.